HOW CSR DISCLOSURE IMPACT ACCOUNTING CONSERVATISM? THE MEDIATING ROLE OF GOVERNMENT OWNERSHIP AND CSR COMITTEE - Suhita Whini Setyahuni; Agus Triyani (Universitas Airlangga, 2026)
This study examines the effect of CSR disclosure on accounting conservatism, with government ownership and CSR committees as moderating variables. Analyzing 185 firm-year observations from 63 listed companies in the mining and energy sectors (2019–2022), we employ Moderated Regression Analysis (MRA) to test the hypotheses. Our findings indicate that CSR disclosure positively affects accounting conservatism. Furthermore, government ownership significantly moderates this relationship, whereas CSR committees do not function as a moderating factor. This research contributes empirical evidence to agency theory by demonstrating the monitoring role of government ownership and introduces a refined measurement for accounting conservatism.